Integrating climate change in agriculture and food security policies and strategies: Experiences and lessons from East Africa - Mungai, Catherine; Radeny, Maren A.O.; Nyasimi, Mary; Atakos, Vivian (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Several African countries are proactively putting in place policies and strategies for climate change adaptation and mitigation in agriculture at national and local levels. In order for policy makers to develop and implement successful climate change policies and programs, they require reliable and timely information on the uncertainties and complexities related to climate change, including risks, and vulnerability. In East Africa, CCAFS scientists have been working with policy makers from 2011 to identify suitable policy and institutional frameworks that support evidence based policy and program development. This entails making available evidence from research to support policy development and implementation at different levels—local, national, regional and global.